EFFECT OF DROUGHT ON THE PERFORMANCE OF THREETURF GRASS SPECIES - Żurek, Grzegorz; Prokopiuk, Kamil; Rachwalska, Agnieszka (Plant Breeding and Seed Science, 2018)
Drought is the main environmental factor hampering world agriculture production. In the face of warming climate and reduced fresh water resources it become obvious that search for any factors decreasing water use is strongly recommended. Turf grasses able to withstand drought period longer could be recommended for turf areas as parks, lawns, home gardens etc. and relatively lower amounts of water should ensure satisfactory turf quality. Therefore, twelve turf varieties from three major cool-season turf grass species: perennial ryegrass (Lolium perenne L.), Kentucky bluegrass (Poa pratensis L.) and red fescue (Festuca rubra L.) were tested in glasshouse pot experiment and in the laboratory for determination of their relative ability to withstand green longer in the face of water deficit. The different response of the examined forms to drought was noted. Conditions that favor fast water depletion were the most suitable for the expression of water deficit-related traits. Therefore, sandy mixture of 16% volumetric moisture content at field water capacity was mostly suitable for observation of the variation of tested forms. Turf condition of Kentucky bluegrass, as contrary to red fescue, was strongly connected with the soil moisture. Different manifestation of drought resistance was observed in tested species. Kentucky bluegrass, as rather no resistant to drought, exposed low level of drought avoidance. Red fescue was able to survive drought mainly due to leaf blades resistant to desiccation. In perennial ryegrass some other mechanisms evolved to survive drought. Early leaf wilting and senescence contributes to nutrient remobilization during drought and avoids large water loses during the transpiration. Therefore, perennial ryegrass turf was able to regenerate better after drought, as compared to the other tested grass species. Search for new turf forms should focus on searching for ability to maintain acceptable conditions longer in a presence of increasing water deficit. It will then reduce the duration of period of poor turf conditions and further, turf water demands.